Stock ranking of companies in the three metals, chemical and pharmaceutical industries with a combined approach of fuzzy SWARA and COCOSO - Hamzeh Amin-Tahmasbi; Mahdi Alireza (تصمیم گیری و تحقیق در عملیات)
Purpose: Choosing stocks has always been one of the investors' concerns. The primary purpose of this study is to identify the factors affecting the decision-making and ranking of stocks in the stock exchange's three metal, chemical and pharmaceutical industries according to the importance of these industries.Methodology: The statistical sample of this research includes the shares of 84 companies in these three industries, which have been examined based on the data of 2021. First, stock rating factors were extracted by reviewing the research background. Experts used these factors in this field, and the final factors were selected after screening. Weighting and prioritization of these factors were done using the fuzzy SWARA method. According to the weight of the factors obtained from the fuzzy ride method and companies' financial information, the COCOSO method was used to rank the target stocks.Findings: The results showed that price-income ratio, operating profit margin, and percentage of return on capital are the essential criteria for experts. Also, Fasabezvar, Fasmin, and Vetoka from the metal group, Vepakhsh, Desobha, and Depars from the pharmaceutical and shoyande, Shepdis and Shefan from the chemical group won the first and third places.Originality/Value: In the last four years, various works have been done in this field, but less work has paid attention to the uncertainty in experts' opinions. Regarding other innovations of this article, it can be pointed out that the three industries of metal, chemical, and pharmaceutical, due to the importance of these industries, have not been specifically studied. Regarding the method of prioritizing criteria and stocks, less attention has been paid to new decision-making methods and uncertainty in decisions. Therefore, using new techniques, the importance of criteria can be determined with higher accuracy, and a better return on investment can be obtained.